Strong effects of uniaxial pressure and short-range correlations in Cr2Ge2Te6 - Spachmann, Sven; Elghandour, Ahmed; Selter, Sebastian; Büchner, Bernd; Aswartham, Saicharan; Klingeler, Rüdiger (Physical review research, 2022)
Cr2Ge2Te6 is a quasi-two-dimensional semiconducting van der Waals ferromagnet down to the bilayer with great potential for technological applications. Engineering the critical temperature to achieve room-temperature applications is one of the critical next steps on this path. Here, we report high-resolution capacitance dilatometry studies on Cr2Ge2Te6 single crystals which directly prove significant magnetoelastic coupling and provide quantitative values of the large uniaxial pressure effects on long-range magnetic order (∂TC/∂pc=24.7 K/GPa and ∂TC/∂pab=−15.6 K/GPa) derived from thermodynamic relations. Moderate in-plane strain is thus sufficient to strongly enhance ferromagnetism in Cr2Ge2Te6 up to room temperature. Moreover, unambiguous signs of short-range magnetic order up to 200 K are found.